Evolução tectônica e estratigráfica das bacias da margem continental do Uruguai - Pérez, Ethel Morales [UNESP] (2013)
The continental margin of Uruguay is a typical divergent margin, generated as the result of the breakup of Gondwana and later opening of the Atlantic Ocean. It is located in the southern extensional segment of the Atlantic margin, where the opening came from the south to the north, during the Jurassic-Early Cretaceous. Three sedimentary basins are located on the continental margin of Uruguay: the Punta del Este Basin, the southernmost part of the Pelotas Basin and the Oriental del Plata Basin. The crustal architecture of the Uruguayan margin presents characteristics of volcanic type passive margins, with the development of SDR wedges and the presence of a high velocity lower crust. The thickness of the continental crust decrease progressively in the strike direction of the Uruguayan continental margin and the passage of continental-oceanic crust came closer to the coastal line in the same direction. Mohorovicic unconformity presents a sharp inflection in the central and northern sectors of the Uruguayan continental margin (Pelotas Basin), associated with thinning of the continental crust and more gradual in the southern sector (Punta del Este Basin). This inflection coincides with the shelf break and the largest gravity anomaly present in the continental margin of Uruguay for each sectors. Fourteen depositional sequences were mapped on the Uruguayan continental margin, using the sequence stratigraphy as a basin analysis method. These depositional sequences were grouped into four phases of evolution: prerift (Paleozoic), rift (Jurassic-Early Cretaceous), transition (Barremian-Aptian) and postrift (Aptian-Present). Each of these phases has a specific structural configuration and stratigraphic architecture, depending of the type of basin, tectonic elements, sediment supply, rate of subsidence and sea level changes. During the geological evolution of the Uruguayan continental margin a migration of depocenters occurred, towards northeast....